A Revision of the Genus Leptophlebia Westwood in North America (ephemeroptera:leptophlebiidae:leptophlebiinae) - Burian, Steven K. (Bulletin (Ohio Biological Survey) ; new ser., v. 13, no. 3, 2001)
Keywords: Classification; Identification; Leptophlebia; Leptophlebia; North America; dept.bio; faculty_collection

Selecting appropriate controls in studies of owl nest-site selection (reply to Marks) - Bosakowski, T.; Smith, D.G. (Journal of Field Ornithology, 2001)
Marks (2001) is critical of our study of nest-site selection in Great Horned Owls (Bubo virginianus) because we compared our data from owl nests with data from random points rather than from unused stick nests. We argue that Great Horned Owls have so many options for nesting in eastern forests that there is little constraint on nest-site selection. Therefore, their choice of nest sites is determined largely by vegetation characteristics in the surrounding landscape, and comparison of owl nests with random points is the best way to assess nest-site selection. Furthermore, we believe that use of unused nests as controls, as advocated by Marks, is biased because control nests will have many of the same characteristics as nests used by owls.
Keywords: Bubo virginianus; Strigiformes; dept.bio

Developmental expression of a voltage-dependent potassium channel (Kv3.1) in auditory neurons without cochlear input. - Feng, Jane; Morest, D Kent (Journal of Neuroscience Research, 2001)
Kv3.1, a voltage-dependent potassium channel, has two forms, -a and -b, which differ in expression during development and at the onset of function in the auditory system. To determine whether cochlear nerve input could affect the expression of these two forms, cultures of the developing cochlear nucleus were explanted in the absence of the cochlear nerve at the beginning of cell migration (Hamburger-Hamilton stage 28-30), while neuroblasts continued to migrate onto the culture substrate. After 8, 15, and 22 days in vitro (three survival groups), cultures were immunostained with antibodies recognizing either both forms of Kv3.1 or only the -b form. Only young and newly migrated nerve cells were sampled. In the three survival groups, all nerve cells expressed Kv3.1, among which only 50% or less expressed the -b form. Some of the more differentiated multipolar cells expressed the -b form, but most were labeled with the antibody that recognizes both forms. Thus, in the absence of peripheral input, both forms of Kv3.1 appear at stages very early in development, although not all cells necessarily coexpress both forms. These results agree with other observations in the chick embryo in situ. They are consistent with previous work implicating Kv3.1 in cell migration during early development.
Keywords: *Cell Differentiation/ph [Physiology]; *Cell Movement/ph [Physiology]; *Cochlear Nerve/em [Embryology]; *Cochlear Nucleus/em [Embryology]; *Gene Expression Regulation, Developmental/ph [Physiology]; *Neurons/me [Metabolism]; *Neuropeptides/me [Metabolism]; *Potassium Channels, Voltage-Gated; *Potassium Channels/me [Metabolism]; Age Factors; Animals; Cell Compartmentation; Cell Compartmentation/ph [Physiology]; Cell Differentiation; Cell Movement; Cell Size; Cell Size/ph [Physiology]; Cells, Cultured; Cells, Cultured/cy [Cytology]; Cells, Cultured/me [Metabolism]; Chick Embryo; Chicken embryo; Cochlear Nerve; Cochlear Nerve/me [Metabolism]; Cochlear Nucleus; Cochlear Nucleus/cy [Cytology]; Cochlear Nucleus/me [Metabolism]; Cochlear nucleus; Denervation; Gene Expression Regulation, Developmental; Immunohistochemistry; Neurons; Neurons/cy [Cytology]; Neuropeptides; Nucleus magnocellularis; Potassium Channels; Potassium Channels, Voltage-Gated; Protein Isoforms; Protein Isoforms/me [Metabolism]; Sensory Deprivation; Sensory Deprivation/ph [Physiology]; Shaw Potassium Channels; Tissue culture; amino terminal sequence; animal cell; article; auditory nervous system; cell differentiation; cell migration; cell survival; chicken; cochlear nucleus; dept.bio; immunohistochemistry; magnocellular nucleus; nonhuman; potassium channel; priority journal; protein expression; tissue culture